World's biggest plant shrinks as hungry deer move in. (25th October 2018) - Unknown
Wily herbivores have breached a fence intended to protect the 43-hectare 'Pando' aspen. Wily herbivores have breached a fence intended to protect the 43-hectare 'Pando' aspen.